Pengaruh Kualitas Pelayanan Jasa Pengiriman Paket terhadap Kepuasan Konsumen pada PT. Pos Indonesia - Paa, Amsal Bernadus; Sinay, Philipus; Jantje, Hendry J. (Attractive : Innovative Education Journal, 2022)
This study aims to analyze the effect of package delivery service quality on consumer satisfaction at PT. Indonesian post. Malawili Aimas Sub-Branch Office, Sorong Regency. The data analysis method used is quantitative descriptive analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study were all consumers at PT. Indonesian post. The Malawili Aimas Sub-Branch Office, Sorong Regency, totaled 590 respondents. The sample was 85 respondents. Primary data were obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 8.704 + 0.619X, the regression coefficient value of 0.619 means that every time there is a change and an addition of one percent in the variable quality of package delivery services, the variable satisfaction consumer satisfaction will increase by 0.619 if the variable quality of package delivery services is zero, then customer satisfaction has a value of 8.704. In the coefficient of determination test obtained R square 58.6%. This means that the quality of package delivery services affects customer satisfaction by 50.1%. while the remaining 49.9% is influenced by other factors not analyzed in this study.The results of the t-test, where tcount tcount 9.239> from ttable 1.6634, it can be said that the variable quality of package delivery services has a positive and significant effect on consumer satisfaction Keywords: Service Quality Package Delivery, Consumer Satisfaction, Service Quality